Nanomedicine: development of a tri-imageable nanoparticle for diagnostics - Bumb, A (2008)
Targeted, controlled, and noninvasive delivery of therapeutics is a major goal of pharmaceutical development. However, few techniques allow imaging and controlled drug release at the cellular level. Herein, a potential targeted drug delivery platform with three imaging reporters has been developed by coupling the magnetic properties of ultrasmall superparamagnetic iron oxide nanoparticles (USPIOs) with near infrared fluorescence of Cy5.5 and γ-emissions of 111In that is chelated to a conjugated antibody. This silica-coated iron oxide nanoparticle (SCION) allows for verification of localization, characterization of nearby physiology, and quantification. During each phase of development, the nanoparticles have been characterized for surface charge, structure, optical response, and magnetic properties. Although the size is an advantage for passive delivery, to actively direct SCIONs to a specific location (i.e. epithelial cancers or multiple sclerosis inflammatory foci), various antibodies have been attached to the particle surface. The chelator CHXA”-DTPA was conjugated to antibody for radioisotope labeling. Cell viability, biodistribution, pharmacokinetics, MR, optical, and nuclear imaging studies were conducted. The results presented demonstrate SCION‟s potential for application in cell tracking and liver imaging, as well as its promise in the area of sentinel node imaging. In vivo optical and magnetic resonance imaging of athymic mice given intracutaneous injection of multimodal SCION in the foot pad reveal visualization of the primary draining lymph nodes. Unlike previous techniques, the particle could first be used to characterize lymph nodes by MR, followed by fluorescence identification during surgery, and further histology using its fluorescence and iron content. As currently synthesized, the nanoparticles can be used for diagnostics; however, they can also be developed into a method of thermotherapy. Once the delivery construct is traced to its target location, its superparamagnetic properties can be exploited by the application of an AC magnetic field to heat tissue or activate a drug. Thus, with conjugates of this nanoparticle, it should be possible to target specific tissues, verify localization and then non-invasively activate multimodal therapies using extrinsic fields.